2013
DOI: 10.5937/turizam1302045r
|View full text |Cite
|
Sign up to set email alerts
|

Spa-wellness center as part of the hotel facility

Abstract: Over the last decades "wellness spa" industry has experienced a boom around the world. The word "Wellness" has been formed by merging two words: "Well Being" + "fitness", and appeared in the thirties of the last century in the United States. The primary objective of this movement is an ancient philosophy, according to which there ´s no fulfilled life without the assent of the physical and mental, also physical and spiritual. Hotel guests, today more than ever, want higher quality offer for their money. This me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Also, the different definitions of spa tourism (Ramos and Untung 2016) do not include an answer or definition of corporate security in the field of spa tourism in terms of the perception of security. Similarly, the concept of corporate security was attempted to be defined or explained by the research managers and stakeholders (Rančić, Popov-Raljić, and Pavić 2013; Škufca, security experts at the Association of Slovenian Natural Spas, interview 2018) through the content of citing examples of their practice and personal experiences. For example, security is often conceptualised in terms of multidimensionality.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the different definitions of spa tourism (Ramos and Untung 2016) do not include an answer or definition of corporate security in the field of spa tourism in terms of the perception of security. Similarly, the concept of corporate security was attempted to be defined or explained by the research managers and stakeholders (Rančić, Popov-Raljić, and Pavić 2013; Škufca, security experts at the Association of Slovenian Natural Spas, interview 2018) through the content of citing examples of their practice and personal experiences. For example, security is often conceptualised in terms of multidimensionality.…”
Section: Discussionmentioning
confidence: 99%
“…The term 'wellness' is defined as a healthy overall lifestyle, including well-being, comfort, and all the activities needed to achieve it, which are marketed as tourist products (Tourism Technical Dictionary). The term is often used to designate a healthy balance of the body and mind resulting in overall well-being (Rančić et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The authors identified the main motivational factors for visiting wellness centres as recreation, relaxation, improvement of quality of life, and social activities (Kim and Batra, 2009). Rančić et al (2013) found that the motives for visiting wellness centres in Slovenia vary among tourists and largely depend on the socio-demographic characteristics of visitors and features of wellness centres (Rančić et al, 2013).…”
Section: Introductionmentioning
confidence: 99%